Vivendo em Manguinhos: a trajetória de um grupo de cientistas no Instituto Oswaldo Cruz Life in Manguinhos: the career trajectory of a group of scientists at the Instituto Oswaldo Cruz - Carlos Eduardo Calaça (História, Ciências, Saúde: Manguinhos, 2001)
Este artigo analisa a trajetória de um grupo de cientistas biomédicos de Manguinhos, centrando-se no processo de construção de suas carreiras profissionais, entre as décadas de 1920 e 1950. Para tanto, detenho-me nos estudos de casos, procurando balizar as estratégias de recrutamento, os meios de sociabilidade e de consolidação, assim como os valores que moldaram a identidade do grupo no interior do Instituto Oswaldo Cruz, um dos principais loci da ciência biomédica no Brasil. This article aims to analyze the career trajectory of a group of biomedical scientists of Manguinhos and it focuses on the process of construction of their professional careers between the 20s and the 50s. It is centered on case studies, with a view to evaluating the sociability and consolidation means employed by the group, the recruiting strategies, as well as the values which shaped their identity in the daily life inside the Instituto Oswaldo Cruz, deemed to be one of the leading loci of biomedical sciences in Brazil.